ANALISIS USABILITY TERHADAP USER EXPERIENCE PADA APLIKASI SAVEMONEY MENGGUNAKAN METODE USE QUESTIONNAIRE - Mahendra, Yusril Raga; Rahman, Syaiful; Arianti, Arianti (STMIK KHARISMA Makassar, 2025)
This study focuses on evaluating the usability of the SaveMoney application concerning user experience. SaveMoney is designed to notify users about their financial expenses and income. Data collection for this analysis involved literature reviews and questionnaires, employing the USE Questionnaire technique, which assesses four criteria: usefulness, ease of use, ease of learning, and satisfaction. The results, measured with a Likert scale, show that Usefulness received a score of 80.08%, Ease of Use scored 83.27%, Ease of Learning was 86.67%, and Satisfaction was 85.33%. These percentages indicate that the application performs well in these areas. Overall, the average percentage across all variables was 83.60%, suggesting that the SaveMoney application meets the standards of the USE Questionnaire.